Analyse Implementation of Inquiry-Based Learning in Physics for Learning Outcomes and Thinking Skills - Nabillah Zuhrotun Nisa; Ikah Mudrikah; Shelvia Junita Putri; Binar Kurnia Prahani; Rizki Fitri Rahima Uulaa (IKIP Widya Darma Surabaya, 2023)
Objective: The Inquiry Based Learning model is one of the learning models that can be applied in today's learning process. In the process of learning not only the learning results are necessary values but also the thinking ability of the student should be taken into account. This Inquiry Based Learning model is a learning model that is centered on the student and requires the ability to think in finding a concept. Therefore, the author is interested in studying further on the implementation of Inquiry Based Learning in the learning process of physics. Method: The method used in this study is conducting a literature study of scientific journal articles, with data analysis using qualitative research. Results: Based on the research that has been done, it can be concluded that by implementing Inquiry Based Learning in the learning process of physics, can improve the learning outcomes and thinking skills of the pupils. So the model of inquiry based learning can be applied in the physical learning process in schools with the expectation of pupils more active in the process of learning and have improved learning results and have the ability to think to solve problems.